Self-control and compulsive buying behavior: The mediating role of ill-being perception - Ankita Jain; Dr.Sandeep Srivastava; Abhishek Shukla (Cogent Business & Management, 2023)
AbstractCompulsive buying is a relatively modern stereotypical disorder that interferes with our daily lives and causes serious mental and financial problems. Most studies provided information on an impulsive characteristic that causes compulsive buying and addiction, whereas a lack of studies was found on the controlling aspect of compulsive buying behavior. Using negative emotion can be the first approach for examining the relationship between self-control and propensity for compulsive purchases. The current study examined the direct influence of self-control on compulsive buying behavior (CBB) as well as the role of ill-being perception as a mediator in the relationship between self-control and CBB. An online survey was conducted to collect relevant data. A total of 639 buyers, both males and females of various ages, completed questionnaires. Correlation and mediation analysis revealed that self-control positively affected compulsive buying whereas ill-being perception negatively influences the CBB. Further, Ill-being perception had a mediating effect on self-control and CBB. The results further showed that to avoid the negative effects of compulsive buying behavior, buyers should be trained to improve self-control by inducing negative emotions related to CBB.